Kebijaksanaan (wisdom) dan fanatisme pada penggemar K-Pop - Salsabela Diema Yorenagea Hayati; Adhyatman Prabowo; Udi Rosida Hijrianti (Cognicia, 2022)
Korean Pop (K-Pop) popularity and huge number of fans have spread globally, including Indonesia. Being a loyal fan providing support for idols is one of the mandatory things for K-Pop fans. Any form of fan activity to support idols excessively can lead to fanaticism. This study aims to examine the correlation between wisdom and fanaticism in K-Pop fans. Sampling was done by purposive sampling technique. The research subjects were a total of 389 subjects, with at least 1 year of experience as fans and were in the range of age 18 - 21 years old. Data collection was delivered out online with google form using the fanaticism scale of K-Pop fans and the adaptation of the 3D-WS wisdom scale. Data analysis was carried out using the Pearson product moment Correlation method which showed there was no correlation between wisdom and fanaticism in K-Pop fans (r= -0.080; p > 0.05).   Keywords: Fanaticism, K-Pop fans, wisdom